Agility path through work values in knowledge-based organizations: a study of virtual universities (2014)
All people enter organizations with a formed personality and some initial experiencesand values depending on the culture, which will, in turn, influence their efficiency and performance.Therefore, great attention must be paid to work values of the employees and the issues which affectthem, especially in organizations that are complex in their structure and culture. Today’s dynamicenvironment requires organizations to be agile in their processes, with the issue being even morecritical in knowledge-based organizations such as virtual universities. In this research, we identifythe path through which organizations can achieve agility by means of work values. Although thereare many dimensions in work values and organizational agility, using the methodology applied inthis research, we omit some of these dimensions and find the best methods that will enable managersto wisely invest in the most important issues and get the best results in the path to achieveagility through work values.